Aerobic exercise performance is impaired in naturally menstruating females compared with males 24 hours following a strenuous aerobic Interval workout - Blough, K.; Rainsberger, K.; Freemas, J. A.; Carter, S. J.; Baranauskas, M. N. (International Journal of Sports Physiology and Performance, 2026)
Purpose: To examine potential sex differences in recovery following strenuous aerobic exercise and to assess associations between recovery and symptoms in female exercisers.